2019
DOI: 10.4236/cmb.2019.93006
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study, Linear and Nonlinear Multiple Regression in the Prediction of HDAC7 Inhibitory Activities on a Series of Hydroxamic Acids

Abstract: In this work, we conducted a QSAR study on 18 molecules using descriptors from the Density Functional Theory (DFT) in order to predict the inhibitory activity of hydroxamic acids on histone deacetylase 7. This study is performed using the principal component analysis (PCA) method, the Ascendant Hierarchical Classification (AHC), the linear multiple regression method (LMR) and the nonlinear multiple regression (NLMR). DFT calculations were performed to obtain information on the structure and information on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Most of the local OM molecules coincides with molecular HOMO, which indicates a high reactivity of the local OM. It is suggested that atom 14 is interacting with a deficient center in electrons through its first two busiest local molecular orbitals [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the local OM molecules coincides with molecular HOMO, which indicates a high reactivity of the local OM. It is suggested that atom 14 is interacting with a deficient center in electrons through its first two busiest local molecular orbitals [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The AD is determined by the response (property) of the compounds and the descriptors in the developed QSPR model . The Williams plot with standardized cross validated residuals ( R ) versus leverage (Hat diagonal) values ( h ) is highly recommended, which is widely used for visualizing the AD. It should be noted that if the h value of a compound in the training set is greater than the threshold value h * ( h * = 3 p / n , where p is the number of model variables plus one and n is the number of the training set data), the structure of this compound reinforces the developed model. , If the most data points are located in the region of 0 ≤ h ≤ h * and −3 ≤ R ≤ 3, the developed model can be considered statistically acceptable and valid.…”
Section: Methodsmentioning
confidence: 99%
“…55−57 It should be noted that if the h value of a compound in the training set is greater than the threshold value h* (h* = 3p/n, where p is the number of model variables plus one and n is the number of the training set data), the structure of this compound reinforces the developed model. 10,58 If the most data points are located in the region of 0 ≤ h ≤ h* and −3 ≤ R ≤ 3, the developed model can be considered statistically acceptable and valid.…”
Section: Methodsmentioning
confidence: 99%